Answer: can you explain what you mean because its just numbers
Answer:
16π or 50.24
Step-by-step explanation:
Area of a circle is πr^2
π*4^2
16π
These are the same line when you graph. So there are infinite solutions to this system.
well, we know it's a line, and to get the equation of any line all we need is two points, let's pick two from the table hmmmm say let's use (-3 , -7) and (3 , 11)
![(\stackrel{x_1}{-3}~,~\stackrel{y_1}{-7})\qquad (\stackrel{x_2}{3}~,~\stackrel{y_2}{11}) \\\\\\ \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{11}-\stackrel{y1}{(-7)}}}{\underset{run} {\underset{x_2}{3}-\underset{x_1}{(-3)}}}\implies \cfrac{11+7}{3+3}\implies \cfrac{18}{6}\implies 3](https://tex.z-dn.net/?f=%28%5Cstackrel%7Bx_1%7D%7B-3%7D~%2C~%5Cstackrel%7By_1%7D%7B-7%7D%29%5Cqquad%20%28%5Cstackrel%7Bx_2%7D%7B3%7D~%2C~%5Cstackrel%7By_2%7D%7B11%7D%29%20%5C%5C%5C%5C%5C%5C%20%5Cstackrel%7Bslope%7D%7Bm%7D%5Cimplies%20%5Ccfrac%7B%5Cstackrel%7Brise%7D%20%7B%5Cstackrel%7By_2%7D%7B11%7D-%5Cstackrel%7By1%7D%7B%28-7%29%7D%7D%7D%7B%5Cunderset%7Brun%7D%20%7B%5Cunderset%7Bx_2%7D%7B3%7D-%5Cunderset%7Bx_1%7D%7B%28-3%29%7D%7D%7D%5Cimplies%20%5Ccfrac%7B11%2B7%7D%7B3%2B3%7D%5Cimplies%20%5Ccfrac%7B18%7D%7B6%7D%5Cimplies%203)
![\begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{(-7)}=\stackrel{m}{3}(x-\stackrel{x_1}{(-3)}) \\\\\\ y+7=3(x+3)\implies y+7=3x+9\implies y = 3x+2](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7B%7Cc%7Cll%7D%20%5Ccline%7B1-1%7D%20%5Ctextit%7Bpoint-slope%20form%7D%5C%5C%20%5Ccline%7B1-1%7D%20%5C%5C%20y-y_1%3Dm%28x-x_1%29%20%5C%5C%5C%5C%20%5Ccline%7B1-1%7D%20%5Cend%7Barray%7D%5Cimplies%20y-%5Cstackrel%7By_1%7D%7B%28-7%29%7D%3D%5Cstackrel%7Bm%7D%7B3%7D%28x-%5Cstackrel%7Bx_1%7D%7B%28-3%29%7D%29%20%5C%5C%5C%5C%5C%5C%20y%2B7%3D3%28x%2B3%29%5Cimplies%20y%2B7%3D3x%2B9%5Cimplies%20y%20%3D%203x%2B2)
Answer:
6 + 4x − x² = 10 − (x − 2)²
the turning point : (2 , 10)
Step-by-step explanation:
6 + 4x − x² = − x² + 4x + 6
= − (x² − 4x) + 6
= − (x² − 4x + 4 − 4) + 6
= − [(x − 2)² − 4] + 6
= − (x − 2)² + 4 + 6
= − (x − 2)² + 10
= 10 − (x − 2)²
Then the turning point of y is (2 , 10)